Manajemen program pengembangan panca jangka, kemandirian dan kemajuan Pondok Modern Darussalam Gontor Indonesia - Katni Katni; Ayok Ariyanto; Sigit Dwi Laksana (AL-ASASIYYA: Journal Of Basic Education, 2020)
This research is aimed at investigating the philosophical meaning of Pondok Gontor's Modern Darussalam using the management of the "Five Term" development program. Exploring the management relations of the "five term" development program, to the independence and progress of Pondok Gontor and, exploring the extent of the results of the "Panca Term" development program of the Pondok Gontor Modern Darussalam in realizing its independence and educational progress. Based on preliminary studies that the management of the development program "Panca Term" Pondok Modern Darussalam Gontor showed its success. Among the results that appear until the age of 90 this year, that PMDG succeeded in producing alumni who became prominent national figures, had 16 branch boarding schools throughout Indonesia, had businesses in the economy quite rapidly, had very large waqf assets, developed Darussalam Gontor University, which until now has succeeded in having S1, S2 and S3 study programs. In addition, his other successes were managed by his marketing to many foreign students and students who sought knowledge in Gontor. Including Pondok Gontor, is in demand by Indonesian elites, such as the children of state officials and national religious leaders. This is what attracts researchers to conduct this research. So it is felt that their presence is needed as a management model for developing Islamic boarding schools in particular and Islamic education in general. The management system model that can be transformed is in preparing strategic plans for the long-term, medium-term and short-term development management models in creating independence and progress in pesantren and Islamic education institutions in general.